Implementation Of Virtual Reality (VR) in Enhancing Students' Speaking Skills - Rosyid, Abdur; Fahri; Zuhri, Fauris; Abida, Fithriyah Inda Nur; Mahardika, I Putu Permana (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2024)
This research seeks to explore the role of Virtual Reality (VR) technology in aiding students to build their speaking skills, as well as to evaluate the effectiveness of VR in enhancing these abilities. The study uses a classroom action research approach with a cyclical model across two cycles, each comprising the stages of planning, implementing actions, observing, and reflecting. Data was collected through performance tests and observations, and analyzed using both quantitative and qualitative descriptive statistics. The results reveal that VR implementation significantly improves students' speaking skills. This improvement is demonstrated by the rise in students' average scores across cycles; the first cycle showed an average score of 66.15 with a classical completeness rate of 60%, while the second cycle increased to an average score of 77.3 with a completeness rate of 80%. These findings suggest that VR is an effective tool for enhancing students' speaking proficiency, offering an immersive and interactive learning experience that fosters greater confidence and engagement in language practice.